0414 Estimated Prevalence of Idiopathic Hypersomnia in the Wisconsin Sleep Cohort. (25th May 2022) - Peppard, Paul; Plante, David; Hagen, Erika; Barnet, Jodi; Mignot, Emmanuel
Abstract: Introduction: Idiopathic hypersomnia (IH) is a neurologic condition characterized by chronic excessive daytime sleepiness despite normal sleep duration in which sleepiness is unexplained by other sleep disorders, behaviors, or other identifiable causes. Population-based prevalence estimates of IH are unavailable, though a recent analysis of a US insured population found 1/10, 000 persons were diagnosed with IH. Here we estimate IH prevalence in the Wisconsin Sleep Cohort (WSC). Methods: The WSC is an epidemiology cohort recruited from a working population. To characterize IH we used measures of subjective (Epworth Sleepiness Scale, ESS) and objective sleepiness (Multiple Sleep Latency Tests, MSLT), polysomnography, sleep diaries, and extensive questionnaires. IH was defined as the union of: ESS>10; MSLT<8 minutes; <2 sleep-onset REM periods; apnea-hypopnea index (AHI)<15 (we also estimated prevalence using an AHI<5 cutpoint); >=6 hours habitual daily sleep; and non-shift worker. Other explanations for sleepiness were also investigated. Results: Among 792 WSC participants (48% female, mean age=59 years [range=40-78 years]), we estimate an IH prevalence=3.8%, 95% CI=2.6-5.4%). We arrived at this estimate thusly: of n=792 participants, n=275 (35%) had ESS>10; of these, n=89 had MSLT<8 minutes; of these, n=71 had <2 sleep onset REM periods; of these, n=35 had an AHI<15; of these, n=33 slept >=6 hours/night; and, of these, n=30 were non-shift workers. Comparing the 30 so-defined "IH participants" to non-IH participants, respectively: 57% (IH) vs. 48% (non-IH) (NS) were female, mean age was 57 vs. 59 years (NS), mean AHI was 4.6 vs. 13.3 (by definition of IH, mean AHI was lower for IH participants), mean sleep duration was 7.6 vs. 7.7 hours (NS), and sedative use prevalence was 3% vs. 10% (NS). No IH participants reported a history of heart failure, heart attack or stroke. Prevalence of IH using an AHI cutpoint of 5 (i.e., IH only classified in participants with AHI<5), we find an IH prevalence of 2.4% (95% CI=1.5-3.7%). Conclusion: Idiopathic hypersomnia may be more prevalent than previously assumed: approximately 2 to 4% of Wisconsin Sleep Cohort participants had evidence of hypersomnia that could not be explained by other sleep disorders, insufficient sleep, shift work or other examined factors. Support (If Any): This work was supported by the National Heart, Lung, and Blood Institute (NHLBI, R01HL62252), National Institute on Aging (NIA, R01AG058680) and the National Center for Research Resources (NCRR, 1UL1RR025011) at the US National Institutes of Health, as well as a grant from Jazz Pharmaceuticals.